Chairmans statement of a Malaysian public university: a critical discourse analysis - Man, Nurafiq Inani; Abdullah, Zulhamri; Mohd Hassan, Nurul Ain; Tamam, Ezhar (Academic Inspired Network, 2019)
This paper introduces and illustrates an interdisciplinary approach in analysing written and spoken texts via a critical discourse analysis (CDA) that provides researchers with a choice of resources to analyse corporate narrative documents to be more systematic and detailed from a linguistic perspective. CDA addresses how the content and linguistic features of texts influence and are influenced by the context of text production, distribution, reception and adaptation, and also by the wider socio-economic context in which texts are embedded. The analysis applies Fairclough’s (2003, 2006) Dialectic-Relational Approach from the chairman’s statement of a Malaysian public university. The aim of the analysis is to discover the grammatical devices that are used to represent an organisation’s activities and the ways in which they may obfuscate social agency (impersonalisation) and to assess entities, social actors and social events (evaluation). The paper provides an insight on how the management uses linguistic and semiotic devices strategically to achieve a variety of economic and political goals through their corporate narrative.